Fabrication of microcomponents by injection molding - Yuan , S.; Ngoi, B. K. A.; Hung, N. P.; Ali, Mohammad Yeakub (2004)
Miniaturization has been and will continue to be the trend of research and development. A number of microfabrication processes have been developed for the realization of three-dimensional microcomponents. Among these techniques, the micromolding process is one of the key technologies for low-cost mass production of sub-millimeter sized components, with structural details in micrometric or even sub-micrometric ranges. Although micromolding is mainly applied for plastic products, this technology can be applied to fabricate ceramic or metal microstructures. This paper is to present the research results of developing a new microreplication process. To fulfill the requirements of the process, a tabletop-molding machine was modified for melt temperature control and cavity evacuation. A mold with self-alignment demolding mechanism was designed and fabricated. A thermal control system was developed to control the mold temperature with  1 oC tolerance. A vacuum unit was developed to evacuate the microcavity before the injection of plastic melt. The vacuum level in the microcavity could reach 340 Pa at the current experimental condition. Focused Ga+ ion beam sputtering, a maskless patterning of material, was used to fabricate microcavity on Ni-Be insert which was then used as a mold insert. Feasibility of the microreplication process was investigated with the replication of polymer microcomponents, such as a microgear, gear-train, etc. For ease of handling, the microcomponent was integrated onto a block. Involute microgears and micro gear-trains with, 20 m core diameter, and 100 m outside diameter were successfully fabricated. The molded microcomponents were removed from the base and observed under a scanning electron microscope and found to be same with the microcavities.